Theory of Change and Results Based Management Framework for Women’s Seed Entrepreneurship - VP, Sahana; Kapur, Aman; Shivhare, Richa; Puskur, Ranjitha; Nayak, Prakash; Tenneti, Suchaita; Khan, Afreen (CGIAR Initiative on Seed Equal, 2024)
India's seed sector, once predominantly public, has gradually expanded into a diverse industry. The informal seed sector involves local, farmer-driven systems where seeds are produced, exchanged, and used within communities without formal regulation. It plays a crucial role in preserving crop diversity and providing seeds, especially in regions where formal systems are limited. The informal seed sector remains dominant in India's seed production system, accounting for 70-90% of seed supply.1The role of the private sector has also notably expanded, growing from 57.28% to 64.46% in seed production from 2017-18 to 2020-21. As of date, approximately 540 private seed companies operate in India2, with roughly 80 of them running research programs, focusing primarily on foundation, certified and truthfully labeled seeds.